PENELITIAN TINDAKAN KELAS MATERI ALJABAR MELALUI PENDEKATAN SAINTIFIK PADA SISWA SMP KELAS VII DI ERA PANDEMI COVID-19 - Enny Yuliani; Ratni Purwasih; M. Afrilianto (IKIP Siliwangi, 2021)
Articles This research is a classroom action research (classroom action research). The problem formulated in this study is how to apply online learning of algebra material to students of SMP Class VII MTS Negeri 1 Cimahi using a scientific approach? The aim is to find out the application of online learning of algebra material to students of SMP Class VII MTS Negeri 1 Cimahi using a scientific approach. The hypothesis of this research action is that online learning of Algebra material in class VII MTS Negeri 1 Cimahi can be applied through a scientific approach. This research was carried out on class VII-G MTS Negeri 1 Cimahi in the academic year 2020/2021 with a sum of 32 understudies. The instrument utilized is a learning result test as a trial of understudies numerical class activity research capacities a issues (questions) that attention more on understudies internet finding out about variable based math, before the activity with an underlying test, after the underlying test the educator and understudy perception sheet activity is held. Student learning activity in the first cycle is inclued in the quite active category with an average value of 67.50. The student's score increased by 22.50 from the initial test score of 45.00. In the second cycle, student learning activities increased to an average of 78.70, an increase of 11.20 compared to the results of the first cycle test scores. Based on the work indicators, it was concluded that the mastery of Algebra concepts in class VII-G students of MTS Negeri 1 Cimahi could be improved through this approach scientific.